Survey schizophrenic patients' satisfaction with antipsychotic medication in Shafa ‎psychiatric center - naeima khodadady; mahin nadem; aemeh eskandari; sedigheh golipuor; moohamadjavad muosavi (Guilan University of Medical Sciences, 2009)
Introduction: Satisfaction with treatment is a criterion for quality of care and it s a referral point ‎for personnel s evaluation. There is limited literature and patient satisfaction is unknown. ‎ Objective: The goal of this study was to survey schizophrenic patients satisfaction with ‎antipsychotic medication in Shafa psychiatric center in ‎‏2007‏‎. ‎ Methods: In this study ‎‏100‏‎ schizophrenic patients hospitalized in different wards of Shafa hospital ‎were chosen. Data collection instrument included a two part questionnaire. The first part with four ‎questions covered personal characteristics and the second part included satisfaction scale with ‎‏32‏‎ ‎questions. Descriptive statistics and Chi-square test were used for data analysis.‎ Results: The findings indicated that there was a significant relationship between satisfaction with ‎treatment and gender (p< ‎‏0.0003‏‎), occupation (p< ‎‏0.0001‏‎), and living condition (p<‎‏0.0001‏‎). ‎Also ‎‏60‏‎% of patients said that they were satisfied with treatment. ‎ Conclusion: Interpersonal relationship between patient and health team and also increased patient ‎participation in treatment program can effect patient satisfaction.‎